Nasal Anatomy and Function - Patel, Ruchin G. (Facial Plastic Surgery, 2017)
The nose is a complex structure important in facial aesthetics and in respiratory physiology. Nasal defects can pose a challenge to reconstructive surgeons who must re-create nasal symmetry while maintaining nasal function. A basic understanding of the underlying nasal anatomy is thus necessary for successful nasal reconstruction.
Keywords: nasal anatomy; nasal function; nasal septum; nasal valve